Process on Khaen Accompaniment for Lam Performance in Lao PDR - Ponkhet, Yothin (Chophayom Journal, 2016)
This research aimed at investigating the following : 1) The instruction process on Khaen accompaniment for Lam performances in Lao PDR 2) The difÞculties and the ways to develop the instruction process on Khaen accompaniment for Lam performances in Lao PDR. Research areas were Vientiane Metropolitan, Khammuan, Savannakhet, and Champasak Provinces. Field data were gained from observation and interviews with 7 key-informants, 28 casual informants, and 6 general informants. The data were examined by means of a triangulation technique, analyzed according to research purposes and research results were presented by means of a descriptive analysis. The research results revealed that the instruction process on Khaen accompaniment for Lam performances consisted of 3 steps : preparation, operation, and evaluation. In preparatory step, the non - schooling students were stimulated by their own interest and acquired Khaens (reed mouth organs) by themselves, whereas the in-schooling students were provided khaens and instruction aid materials by their teachers. In operational step, the non-schooling students learned to play the khaens by themselves through listening and observing from non-particular teachers performances, then they started to perform from their memories, whereas the in-schooling students learned to play the khaens under the supervision of their teachers. In evaluative step, the non-schooling students were evaluated by peers and professional molams (Lao-folk singers), whereas the in - schooling students were evaluated by their teachers.